Potential factors influencing increasing numbers of Canada Geese Branta canadensis in west Greenland - Fox, Anthony D; Mitchell, Carl; Weegman, Mitch D; Griffin, Larry R; Stroud, David A; Francis, Ian S (Wildfowl, 2013)
This paper reviews the increase in abundance of Canada Geese Branta canadensis, particularly those of the subspecies interior, in west Greenland over the last 20 years. Potential reasons for the increase, such as displacement from traditional breeding areas on mainland North America and regional variation in the breeding success of the population are discussed. Breeding biology of Canada Geese nesting in Isunngua, west Greenland (67°N) was monitored for the first time in 2010. The geese had identical mean first egg dates (27 May 2010) but greater mean clutch size compared to those nesting 1,300 km further south at Ungava (58°N) in the same year (4.57 and 3.80 eggs, respectively). Mean May temperatures in Isunngua were on average 2°C higher than in Ungava during 1979–2010, suggesting that females may have been able to enhance reproductive investment in Isunngua relative to Ungava in those years. Moreover, although data are currently only available for one year in Greenland, nesting success there was as high as in other parts of the Canadian range of this subspecies. Compared to the traditional Canadian nesting grounds, milder spring conditions, potentially lower predation rate, availability of abundant food and lack of competition for nest sites may have combined to help explain the rapid expansion of this goose population in west Greenland.